Rationale and design of the Cardiovascular Inflammation Reduction Trial: A test of the inflammatory hypothesis of atherothrombosis - Everett, Brendan M.; Pradhan, Aruna D.; Solomon, Daniel H.; Paynter, Nina; MacFadyen, Jean; Zaharris, Elaine; Gupta, Milan; Clearfield, Michael; Libby, Peter; Hasan, Ahmed A.K.; Glynn, Robert J.; Ridker, Paul M. (The American heart journal, 2013)
Inflammation plays a fundamental role in atherothrombosis. Yet, whether direct inhibition of inflammation will reduce the occurrence of adverse cardiovascular outcomes is not known. The Cardiovascular Inflammation Reduction Trial (CIRT) (ClinicalTrials.govNCT01594333) will randomly allocate 7,000 patients with prior myocardial infarction (MI) and either type 2 diabetes or the metabolic syndrome to low-dose methotrexate (target dose 15-20 mg/wk) or placebo over an average follow-up period of 3 to 5 years. Low-dose methotrexate is a commonly used anti-inflammatory regimen for the treatment of rheumatoid arthritis and lacks significant effects on lipid levels, blood pressure, or platelet function. Both observational and mechanistic studies suggest that low-dose methotrexate has clinically relevant antiatherothrombotic effects. The CIRT primary end point is a composite of nonfatal MI, nonfatal stroke, and cardiovascular death. Secondary end points are all-cause mortality, coronary revascularization plus the primary end point, hospitalization for congestive heart failure plus the primary end point, all-cause mortality plus coronary revascularization plus congestive heart failure plus the primary end point, incident type 2 diabetes, and net clinical benefit or harm. CIRT will use standardized central methodology designed to ensure consistent performance of all dose adjustments and safety interventions at each clinical site in a manner that protects the blinding to treatment but maintains safety for enrolled participants. CIRT aims to test the inflammatory hypothesis of atherothrombosis in patients with prior MI and either type 2 diabetes or metabolic syndrome, conditions associated with persistent inflammation. If low-dose methotrexate reduces cardiovascular events, CIRT would provide a novel therapeutic approach for the secondary prevention of heart attack, stroke, and cardiovascular death.